EVALUASI KESESUAIAN LOKASI POSKO PEMADAM KEBAKARAN DI KECAMATAN SERPONG, KOTA TANGERANG SELATAN (Universitas Esa Unggul, 2016)
The problem of fires in various big cities has become one of the serious problems for urban areas in Indonesia. This is evidenced by the high rate of fire incidence in several big cities, while the fire department's capacity / capacity has not been able to provide better service to the demands of each city. This can have an impact on government efforts in realizing sustainable development. The current Fire Problem is how Fire Fighting can reduce as little as possible the losses incurred in the form of wealth or life in every fire incident with the preparedness and speed of emergency response for each community service through the prevention of fire and other hazards by referring to the rules set by the government . The analysis technique in this study uses model simulation in the form of application from ArcGIS 10.1 software. In this modeling will analyze from some base map which is spatial data which have big influence to optimal location of facility. The concept of the model is started with spatial data input, which will then be processed spatially. Spatial process in the form of changing the map format and also overlay, but the overlay in this model is done automatically by the computer. The research concludes that the firefighting post is suitable and can meet the standard response time of 15 minutes to reach the serpong and Setu sub-districts.Â Keywords: fire, response time, GIS